The Success of Village Fund Allocation for Tourism Village Development in Nglanggeran Village, Yogyakarta - Huda Safira (Pravda: Social Science Interdisciplinary Journal, 2026)
Background. Nglanggeran Village, Yogyakarta, has emerged as one of Indonesia's prominent community-based tourism destinations. Its transformation into a leading tourism village has been strongly supported by the effective utilization of the Village Fund Allocation (ADD). The success of this development model highlights the importance of planned, transparent, and participatory fund management in achieving sustainable rural development. Purpose. This study aims to examine the role of the Village Fund Allocation (ADD) in transforming Nglanggeran into a leading tourism village and to analyze how fund management strategies contribute to local economic growth, environmental sustainability, and cultural preservation. Method. The study employed a qualitative research approach based on literature review. Data were collected from various secondary sources, including academic journals, books, research reports, and news articles related to Nglanggeran Tourism Village and the impact of Village Fund Allocation on its development. Results. The findings indicate that the effective use of Village Fund Allocation has supported the development of tourism-supporting infrastructure, human resource training, and local potential-based programs. This strategic utilization has increased community income, strengthened local participation, and encouraged environmental and cultural preservation. The participatory and transparent governance model implemented in Nglanggeran has played a significant role in ensuring sustainable tourism development. Conclusion. The study concludes that the success of Nglanggeran Tourism Village is closely linked to the strategic, transparent, and community-oriented management of Village Fund Allocation. Sustainable rural tourism development requires not only financial support but also strong local governance, community participation, and a commitment to preserving environmental and cultural assets.